1997
DOI: 10.1364/ol.22.000528
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroadband chirped mirrors for femtosecond lasers

Abstract: We report on the performance of widely tunable femtosecond and continuous-wave Ti:sapphire lasers that use a newly developed ultrabroadband mirror set. The mirrors exhibit high reflectivity (R > 99%) and smooth variation of group delay versus frequency over a wavelength range from 660 to 1060 nm. Mode-locked operation with pulse durations of 85 fs was achieved from 693 to 978 nm with only one set of ultrabroadband mirrors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Recently it was shown that ultrabroadband chirped mirrors can be made that exhibit negative GDD and positive TOD (Fig. 7b), while having a reflectivity exceeding 99% over a bandwidth of 600-1100 nm [63,98]. This means that a combination of chirped mirrors and a prism compressor provides flexible control over TOD across a large spectral range [63].…”
Section: Compressor Designmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently it was shown that ultrabroadband chirped mirrors can be made that exhibit negative GDD and positive TOD (Fig. 7b), while having a reflectivity exceeding 99% over a bandwidth of 600-1100 nm [63,98]. This means that a combination of chirped mirrors and a prism compressor provides flexible control over TOD across a large spectral range [63].…”
Section: Compressor Designmentioning
confidence: 96%
“…Third, the output coupler OC has been placed at the nondispersive end of the cavity, providing an additional output at 82 MHz. Last, we have saved space by replacing the output (cavity-dumped) pulse pre-compressor, consisting of four prisms [50], with two chirped mirrors [63].…”
mentioning
confidence: 99%
“…Dielectric mirrors exhibiting relatively high GD on reflection, however, are not exclusively used in ultrashort pulse laser systems. UBCM structures [7] are widely used in broadly tunable CW or ns pulse lasers or in optical parametric oscillators and amplifiers for beam steering or feedback over a wide frequency range. In these applications, linear absorption loss, subsequent heating, and mirror damage could be critical issues.…”
mentioning
confidence: 99%
“…Proportionality between the absorptance and the GD is very important for application of ultrabroadband chirped mirrors (UBCMs) [7] or highly dispersive mirrors [8] in high power, pulsed laser systems: these mirrors are used for broadband feedback and dispersion compensation, and their reflection GD is typically one or two orders of magnitude higher than that of the low-dispersion QW stacks. However, low reflection loss is crucial in case of dielectric mirrors designed for such lasers: the absorbed power of the laser beam is transformed to heat, which can lead to wavefront distortion or, worse, damage to the coating due to a linear absorption process, which is the dominating damage mechanism for >50 ps pulse durations [9] .…”
mentioning
confidence: 99%
See 1 more Smart Citation